STATISTICAL STUDY OF INTERNATIONAL FINANCIAL ASSISTANCE - HRYTSUN, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ukraine’s signing of the Association Agreement with the EU reflected the country’s desire to be part of the European community through political association and economic integration based on common values, which are the rule of law and respect for human rights and freedoms. To some extent, the obligations under the Association Agreement are a road map for reforming the country, enshrined in an international treaty [1, p. 6]. Over the past four years, Ukraine has made significant progress in the implementation of reforms designed to promote economic growth and increase the welfare of the population. A significant part of these reforms was directly or indirectly implemented to implement the Association Agreement. The government has made progress in energy reform and public administration reform. A new public procurement system was introduced, a strategy for reforming the state finance management system was adopted, etc. In general, the EU provides support to Ukraine under various programs and using a number of mechanisms: technical assistance, budgetary support, macro-financial assistance, project financing. An important role is also played by the Ukraine Support Group, which is not only involved in providing support, but also provides political support for important reforms. The purpose of the study is to analyze the statistical indicators of international financial assistance. It is established that international financial organizations take an important place in the world economy and international economic relations, and their activities contribute to strengthening macroeconomic stability. Expanding Ukraine’s cooperation with the EBRD requires improving the quality of project preparation and documentation, creating a transparent system for monitoring the use of investment resources, increasing the efficiency of government as an important prerequisite for reducing the risks of investors and creditors.